International accounting standards explained - International Accounting Standards Committee (New York : Wiley, 2000)
An introduction to IASC and to the requirements of the IAS which outlines how the standards are used on a daily basis by companies in preparation of their financial statements. and offers a detailed description of the International Accounting Standards Committee and how it is structured. It examines the use of IAS from a practice orientation and looks at the main components of the financial statements, including questions of recognition and measurement of key financial statement items. There is also a discussion of the IASC Framework for the Preparation and Presentation of Financial Statements. The framework provides a foundation for the development of new standards and is used as reference for applying IAS in the absence of detailed application guidance.
Includes bibliographical references and index.
oif 30/03/15
Loan
Keywords: Accounting -- Standards